Pengaruh Metode Total Physical Response pada Perkembangan Kosakata Bahasa Inggris Anak Usia Dini (PIAUD IAIN Kudus, 2021)
Since English has become an international language, more people are learning English in Indonesia and even English is taught from an early age. This is supported by the fact that many children learn foreign languages when they are very young. There are more tutoring places for the introduction of English to children, not only from schools. Therefore, the introduction of English to children varies, one of which is using the Total Physical Response (TPR) method. This study aims to determine whether there is an influence between the development of children’s vocabulary with the TPR method using the pre-experiment research method (one group pretest-posttest). The results of the assessment will be tested by conducting a t-test through SPSS-20. Based on the results of the study, there is an influence between the TPR method on the development of children’s English vocabulary, it can be seen from Ho is rejected and Ha is accepted, which means that there is an influence between the TPR method on the development of children’s English vocabulary, with the values of Sig. (2-tailed is 0.000 < 0.05, with a pretes percentage result of 18.5% while the postes percentage score is 27.5%.